Soil as a sink for carbon sequestration: How agroforestry can help? - Sharrna, U.C.; Sharma, Vikas (Indian Journal of Agroforestry, 2020)
Soils can be a major source or sink of atmospheric CO2 depending upon the land use and management. Soils are an Important sink of CO2 and CH. through conversion to a restorative land use and adoption of recommended management practices which create positive C and elemental (N, P, S, K) budgets. Increasing the C pool of the pedosphere by 10% over the 21st century (+250 billion tons) can create a decrease of 110 ppm of atmospheric CO2, The analysis of C stocks from various parts of the world showed that significant quantities of C (1.1-2.2 Pg) could be removed from the atmosphere over the next 50 years if agroforestry systems are implemented on a global scale. Perennial systems like home-gardens and agro-forests can store and conserve considerable amounts of C in living biomass and also in wood products. In the absence of direct competition between trees and crops for growth resources, sequential agroforestry systems offer an opportunity for exploiting the potential soil ameliorative attributes of trees for enhancing crop production. There is a strong relationship between land-use and carbon stocks. After conversion from forest to other usages, there is a decrease in soil carbon content and increased carbon flux relative to storage. Watershed carbon dynamics indicates that due to intense land use change, Himalayan watersheds are becoming a net source of carbon to the atmosphere. Proper land-use management, restoration of forests and afforestation of wastelands could be a significant step to allow carbon sequestration in mountain watersheds. Agroforestry will be the appropriate land use which would ensure food security and carbon sequestration.